EFFECT OF ASTAXANTHIN IN ANIMAL MODELS OF ANXIETY AND DEPRESSION - DR. REKHA MEHANI; MAJOR (DR.) V. K. YADAV (International Journal of Pharma and Bio Sciences, 2014)
To study anxiolytic and antidepressant effect of Astaxanthin as an adjuvant to standard drug.In this study, to investigate the effects of astaxanthin on anxiety and depression,we performed some behavioural trials including elevated plus maze test, hole-board test, forced swim test, and tail suspension test.Astaxanthin ( 3 mg/kg/day for 15 days, orally) significantly increased the time spent in open arms in the elevated plus maze test and increased the head-dipping count in the hole-board test and significantly decreased the immobility time in the forced swim test and the tail suspension test.In rats, Astaxanthin exerted anxiolytic effects, and also antidepressant activity when given as an adjuvant with standard drugs.